Clinical Skills Training in the Community: Lesson Learned from Diponegoro and Gadjah Mada University - Tri Nur Kristina; Widyandana Widyandana (MEDIA MEDIKA INDONESIANA, 2011)
ABSTRACTBackground: Community-based education (CBE) clerkship in Faculty of Medicine Diponegoro University (FMDU) is implemented after finishing clinical rotation in tertiary hospital, whereas in Gadjah Mada University (FMGMU), is a part of clinical rotation. To have insight information of this difference method, the CBE clerkship in FMDU and FMGMU were compared.Methods: Close and open-ended students’ questionnaires were administered in the end of CBE clerkship.Results: Response rate to the questionnaire was 97.8% (n=286). FMDU students reported the most unprepared skills for CBE clerkship was blood smear of malaria, whereas FMGMU’s students reported management of PHC centre. Both students perceived that they are well prepared in communication skills, management of communicable diseases, and several clinical skills, and also reported that they have frequent experience in outpatient department. FMDU’ students perceived that CBE clerkship gave opportunity to work independently, and they felt more prepared to work as a doctor in the community. On the other hand, FMGMU students felt not so confident in patient management, and reported that supervisor did not give enough assistance. They suggested that CBE clerkship should be done at least after clinical rotation in two Departments, i.e.: Internal Medicine or Paediatric andSurgery or Ob-gyn.Conclusions: CBE clinical clerkship required students’ confidence and independency. Preparation should be done properly not only for the students but also supervisor in the community. Tertiary hospital, which has enough skillful supervisors, is important to train basic clinical skills to students before sending them to the community.Keywords: Clerkships, clinical skills, medical students, CBE, communityABSTRAKKepaniteraan klinik di masyarakat: pembelajaran di Universitas Diponegoro dan Gadjah MadaLatar belakang: Kepaniteraan klinik di masyarakat di Fakultas Kedokteran Universitas Diponegoro diimplementasikan setelah mahasiswa kedokteran tingkat akhir menyelesaikan rotasi klinik di rumah sakit pendidikan tersier, sedangkan di Universitas Gadjah Mada kepaniteraan klinik di masyarakat menjadi bagian dari rotasi klinik. Dalam rangka mendapatkan informasi yang mendalam mengenai perbedaan metode tersebut, kepaniteraan klinik di masyarakat pada ke-2 institusi tersebut dievaluasi dan dibandingkan.Metode: Penelitian kuesioner dengan pertanyaan tertutup dan terbuka, diberikan pada mahasiswa di akhir dari kepaniteraan klinik di masyarakat.Hasil: Kuesioner yang dikembalikan sebesar 97,8% (n=286). Mahasiswa FK Undip melaporkan bahwa yang paling kurang dipersiapkan untuk kepaniteraan kinik di masyarakat adalah keterampilan dalam melakukan pemeriksaan darah hapus malaria, sedangkan mahasiswa FK UGM melaporkan bahwa mereka kurang dipersiapkan dalam hal manajemen puskesmas. Mahasiswa dari ke-2 institusi sama-sama merasa bahwa mereka cukup dipersiapkan dalam hal keterampilan komunikasi, manajemen penyakit infeksi, dan beberapa keterampilan klinik. Mereka juga sama-sama melaporkan pengalaman yang cukup sering di poliklinik. Mahasiswa FK Undip merasa bahwa kepaniteraan klinik di masyarakat memberi kesempatan pada mereka untuk bekerja secara independen, dan merasa lebih siap untuk bekerja sebagai dokter di masyarakat. Di lain pihak, mahasiswa FK UGM merasa kurang percaya diri dalam mengelola pasien dan melaporkan bahwa supervisor di puskesmas kurang memberikan supervisi. Mereka menyarankan agar kepaniteraan klinik di masyarakat dilakukan setelah minimal menjalani rotasi klinik di 2 departemen, misalnya:interna/pediatrik dan bedah/kebidanan.